The Race to Get In, and the Struggle to Get Out: The Problem of Inter-Generational Poverty in Federal Housing Programs - Matthew Shin (Washington University Journal of Law & Policy, 2012)
"Escap[ing] public housing projects" is a colloquial phrase describing the plight of people struggling to ―escape‖ publicly subsidized housing projects and assistance programs. This feat often entails overcoming obstacles of considerable magnitude. Even in a modestly performing economy, a given federally subsidized tenant will find innumerable obstacles between her situation, a decent job, and the ability to live independently. Given society‘s tendency to perceive those in lower classes negatively, not enough credit is given to the plight of the publicly subsidized tenant. Consider the predicament of a low-income single mother. Consider the standard costs of raising a child—physician‘s visits, formula, diapers, and—especially for single parents—day care. Now consider the plight of a low-income, single mother of a disabled child. In addition to the standard costs of child rearing, she is now faced with the additional emotional and economic costs of raising a disabled child. In both instances, the situation poses an impossible set of circumstances. If a mother misses a day of work, it may at best only be the loss of a day‘s pay. But, if her child is disabled and chronically ill, repeated absences are likely to lead to employment termination. Self-sufficiency in these instances seems little more than an impossible dream. This Note will discuss the issue of inter-generational poverty among the participants of federal housing subsidies and public housing systems. In particular, it will focus on tenants participating in public housing and voucher-based housing subsidies. The Note will also explore and comment on the benefits and shortcomings of related statutes such as the Anti-Drug Abuse Act and the Quality Housing and Work Responsibility Act. Ultimately, this Note concludes that existing conditions on assistance are inadequate, and more rigorous, goal-oriented conditions on housing assistance are necessary to address the issue of inter-generational poverty.
Keywords: public housing projects; publicly subsidized housing; inter-generational poverty; Anti-Drug Abuse Act; Quality Housing and Work Responsibility Act